Teachers' Perception towards Students' Learning Behavior after Online Learning - Cemara, Firnanden Darma; Barella, Yusawinur; Aminuyati, Aminuyati (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to determine teachers' perceptions of students' learning behavior after online learning at MTs Negeri 2 Sekadau. The research approach used is descriptive qualitative research. The data sources used are primary and secondary data. The primary data includes three teachers and the headmaster of MTs Negeri 2 Sekadau, while the secondary data consists of document archives related to the research. The data collection techniques used in this research are observation, interviews, and documentation. The documentation is done using a mobile phone camera. The data analysis techniques include data reduction, presentation, and conclusion drawing. The results of this research indicate that the students' learning behavior after online learning has shown positive and negative changes. The positive aspect is that the students are able to learn independently even after online learning, making it easier for teachers to deliver learning materials. The negative changes in learning behavior include laziness, failure to complete assignments, late attendance, and lack of focus during learning. However, the teachers and the school have tried to improve the students' learning behavior after online learning, such as providing advice and imposing sanctions on students who frequently skip classes and rarely submit assignments.